Performing under pressure: The effects of physiological arousal, cognitive anxiety, and gaze control in biathlon - Vickers, J. N.; Williams, A. M. (Journal of Motor Behavior, 2007)
The authors provide evidence that choking under pressure is associated with changes in visual attention. Ten elite biathlon shooters were tested under separate low-pressure (LP) and high-pressure (HP) conditions after exercising on a cycle ergometer at individually prescribed power output (PO) levels of 55%, 70%, 85%, and 100% of their maximum oxygen uptake. The authors determined difference scores by subtracting each athlete's score in the LP condition from his or her score in the HP condition for heart rate (d-HR), rate of perceived exertion (d-RPE), cognitive anxiety (d-CA), and cognitive worry (d-CW), and final fixation on the target or quiet eye gaze (d-QE). Using regression analysis, the authors determined predictors of accuracy for each HP PO level. At PO 55%, the authors found 3 predictors (d-HR, d-RPE, d-QE) that accounted for .62 of the adjusted R2 variance. Accuracy was higher when d-QE was lower and d-RPE and d-HR were higher than the values found in the LP condition. At PO 100%, however, an increase in d-QE and d-RPE accounted for .58 of the adjusted R2 variance. Accuracy was dependent on an increase in external focus (positive d-QE) independently of heart rate. At the highest PO level, directing visual attention externally to critical task information appeared to insulate the athletes from choking under HP.